1980
DOI: 10.1017/s0021859600028501
|View full text |Cite
|
Sign up to set email alerts
|

Changes in albumin, globulin, glucose and cholesterol concentrations in the blood of dairy cows in late pregnancy and early lactation and relationships with subsequent fertility

Abstract: Weekly blood samples were collected from 42 Friesian cows between 5 weeks before and 10 weeks after calving, and analysed for serum cholesterol, albumin, total protein, glutamate-dehydrogenase, sorbitol-dehydrogenase and ornithine-carbamyl-transferase and blood glucose.Cholesterol concentrations increased 2^-fold during the first 8 weeks of lactation. There was also a transient decrease in glucose concentration at calving, but there was no relationship between conception rate and the concentrations of these tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
14
0
1

Year Published

1981
1981
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 22 publications
7
14
0
1
Order By: Relevance
“…Regarding the concentration of albumin at calving, some authors found a decrease in some but not in all cows studied (Rowlands et al 1980) while others found a general decrease (Little, 1974;Rowlands & Manston, 1983;Park et al 2010;Grünberg et al 2011). Regarding the concentration of albumin at calving, some authors found a decrease in some but not in all cows studied (Rowlands et al 1980) while others found a general decrease (Little, 1974;Rowlands & Manston, 1983;Park et al 2010;Grünberg et al 2011).…”
Section: Discussionmentioning
confidence: 92%
“…Regarding the concentration of albumin at calving, some authors found a decrease in some but not in all cows studied (Rowlands et al 1980) while others found a general decrease (Little, 1974;Rowlands & Manston, 1983;Park et al 2010;Grünberg et al 2011). Regarding the concentration of albumin at calving, some authors found a decrease in some but not in all cows studied (Rowlands et al 1980) while others found a general decrease (Little, 1974;Rowlands & Manston, 1983;Park et al 2010;Grünberg et al 2011).…”
Section: Discussionmentioning
confidence: 92%
“…The Relationships between the Fertility of Dairy Cows 609 different clinical and biochemical measurements as indicators of nutritional energy balance, and have then related them to the cows' fertility (for references see ROWLANDS, 1980). There have been experiments which indicate that low blood glucose (MCCLURE, 1968(MCCLURE, , 1970RICHARDS et al, 1987), increased ketone bodies (REFSDAL, 1977;ANDERSON and EMANUELSSON, 1985), low serum albumin ( ROWLANDS et al, 1980), high blood urea (FERGIJSON et a]., 1988), high or low serum phosphorus (HEWETT, 1974;PUGH et al, 1985), other mineral imbalances ( PUGH et al, 1985), reduced liver function ( REID et al, 1979), reduced bodyweight (MCCLURE, 1970HEINONEN et al, 1988), energy deficit (VILLA- GODOY et al, 1988;BUTLER and SMITH, 1989) and overfeeding with protein ( HEWEIT, 1974;CHALUPA, 1984) can all be related to fertility problems.…”
Section: Introductionmentioning
confidence: 99%
“…The plasma concentration of calcium is close to the dependency of endocrine control, which is likely to mask the effects of short-term changes in dietary intakes [6].…”
Section: Discussionmentioning
confidence: 90%